The importance of vaccination in the specific prevention of children and adolescents - London , Isabela Barreiros; Mocelin , Manuela de Queirós Mattoso; Villela , Maria Fernanda Alencar; Andrade , Julia Anholeto de (Seven Editora, 2023)
Specific prevention is one of the levels of primary prevention, characterized by actions during the pre-pathogenic period on pathogens and their vectors. Among the various forms of specific protection, we have vaccination, which consists of the application of etiological agents or parts thereof, such as viruses and bacteria, living or dead, and is currently considered the most efficient way of protection against infectious diseases, given that the stimulus for the production of antibodies occurs. Thus, after being tested and approved for efficacy and safety, each and every vaccine is recommended by the health authorities and legally considered an essential health measure. DOI:https://doi.org/10.56238/alookdevelopv1-161